Farmer heterogeneity and differential livelihood impacts of oil palm expansion among smallholders in Sumatra, Indonesia - Vijesh V. Krishna; Michael Euler; Hermanto Siregar; Zakky Fathoni; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
The study examines the heterogeneous livelihood impacts of oil palm expansion among smallholder farmers in Jambi Province, Sumatra. Per-capita annual consumption expenditure (PACE) is chosen as a quantitative measure of livelihood status of farm-households. Its determinants are estimated using standard treatment-effect and endogenous switching regression models. After controlling for self-selection bias, adopters of oil palm are found increasing their PACE significantly in comparison to the counterfactual. On the other hand, most of the non-adopters are better-off without oil palm, presenting a strong case of comparative advantage. Differential consumption impacts of observed variables are evident across adoption and non-adoption regimes. In general, farm-households with higher opportunity cost of family labour benefit disproportionately more with oil palm adoption.
urn:nbn:de:gbv:7-webdoc-3956-5
Keywords: O12; O33; Q12; P36; R14; 330; adoption; agricultural development; endogenous switching; impact; Indonesia; farmer welfare